The United Nations and Global Public Goods: Historical Contributions and Future Challenges. - Bruce Jenks (Revue Internationale de Politique de Développement)
Published by Palgrave MacmillanThis chapter explores the thesis that the United Nations’ (UN) most important contribution to the production of global public goods has been its role in creating the space and capacity to generate shared values. Starting with the UN Charter itself, the chapter traces the evolution of this contribution through different historical phases. It analyses the impact of globalisation on the role of the UN; in particular it identifies the quality of porousness as a product of globalisation which is critical to understanding the current challenges faced by the UN as well as central to the global public goods agenda. Through this lens the author briefly reviews the evolution of the UN’s role in the fields of peace and security, human rights and development cooperation. He concludes by identifying eight levers for change that will determine the UN’s ability to contribute significantly to the global public goods: the generation of norms and shared values, the quality of leadership, improved governance, innovative financing, institutional realignment, the further consolidation of legal instruments, focus, and the power of networks.